Physicochemical Properties of Magnesium-doped Hydroxyapatite Nanoparticles Prepared by Incipient Wetness Impregnation Method - Jutharatana Klinkaewnarong (Science Faculty of Chiang Mai University, 2019)
Nanocrystalline hydroxyapatite powders are successfully synthesized by sol-gel method with calcination temperature at 600 °C for 2 h. The molar ratio of Ca: P is kept at 1.67 as hydroxyapatite (HAp). Different weight percents of the magnesium-doped hydroxyapatite (xMg/HAp, x = 0, 1, 3, 5, 7 and 9 wt.%) were prepared via incipient wetness impregnation method. The physicochemical properties of the xMg/HAp were investigated by X-ray diffraction (XRD), Energy dispersive X-ray spectroscope (EDX), Transmission electron microscope (TEM), Fourier transform infrared spectroscope (FT-IR) and UV-vis diffuse reflectance spectroscope (UV-vis DRS). The XRD measurement showed that the magnesium ion was homogeneously incorporated into the hexagonal structure of HAp and the lattice parameters, a and c, are in the ranges of 0.9356-0.9396 and 0.6846-0.6869 nm, respectively. Beta-tricalcium phosphate (b-TCP, Ca3(PO4)2) was detected at all compositions and calcium oxide (CaO) was detected with the doped Mg2+ greater than 1 wt.%. The EDX analyses showed that the Ca/P molar ratio gradually decreased with increasing amount of Mg, whereas the (Ca+Mg)/P molar ratio increased. The FT-IR and UV-vis DRS techniques confirmed the formation of HAp. Doping of Mg2+ up to 5 wt.% resulted in the formation of 68-123 nm particles of spherical shapes, while the spherical and rod-like shapes were obtained at 7 and 9 wt.% Mg2+, with their width of 46 and 75 nm, respectively.